O discurso jornalístico sobre os bloqueios das rodovias brasileiras pós-eleições presidenciais de 2022 - Brito, Sabrina Nayara de Lima (2024)
This research aims to analyze the discourse present in news about the highway blockades in Brazil during the week following the elections by two national media groups: Jornal Folha de S. Paulo, from Folha Group, and Jovem Pan, from Jovem Pan Communication Group. The specific objectives of this research were, first, to identify the emergent themes in the discourse from the two media groups, then analyze the global coherency from each group news set, and, finally, to compare the group's discourses' political-ideological positions, considering the news global coherency of meaning. Therefore, it adopted the Critical Discourse Studies (CDS) premises (Van Dijk, 2003, 2008, 2011, 2020). The analysis categories employed were the macro category of discourse meaning, which includes the category of themes. Additionally, we utilized the notion of global coherence, as proposed by Van Dijk (2003), that a collection of texts from an individual or institution may reveal coherence, further exposing their ideological position. As the analyses result, it became evident that the two groups initially positioned themselves in distinct ideological fields, with Folha de São Paulo characterizing the blockades as coupist and anti-democratic actions, and Jovem Pan portraying them as protests of discontent, initially presenting a less incisive ideological marking. In a second moment, Jovem Pan realigned its political-ideological stance in its discourse in response to the pressure from the social context that emerged, also considering them anti-democratic and illegal.